Difference in general behaviour and social interactions of young Yorkshire gilts in different social environments - Hannius, Linda Marie (2019)
In Sweden, there was a switch of breeding material for pigs in year 2012 where Swedish producers were introduced to the Dutch Yorkshire (DY) instead of the Swedish Yorkshire (SY). Gestating sows have, in Sweden, been kept in group housing since the 1980s while DY gilts on the contrary have been kept in individual stalls. Consequently, the genetic selection of these lines of Yorkshire pigs was conducted in different environments and are thus indirectly selected for behaviours beneficial for each respective environment. This may induce behavioural differences between them, which may be of importance in group housing systems. In the wild, piglets usually have the opportunity to socialise with other pigs outside the litter and piglets that can socialise outside the litter have better social skills later in life. Piglets that do not have the opportunity to engage in social interactions outside the litter may behave differently than piglets that have that opportunity.